Efficacy of enriched diets on the larval development and survival of an edible crab, Charybdis lucifera (Fabricius) - Kannupandi, T; Ravi, A Veera; Soundarapandian, P (Indian Journal of Fisheries, 2011)
The live feeds viz., Brachionus plicatilis and newly hatched Artemia nauplii were enriched with an emulsion of cuttle fish liver oil and lecithin and fed to zoea of edible crab Charybdis lucifera. The larvae fed with the enriched feeds showed survival rate of 33% as against 10% in the larvae fed with control diet, with corresponding reduction in larval mortality between the III and IV zoeal stages. The development was completed within 21 days when the larvae were fed with enriched live feeds as compared to 28 days in the control.